Mitochondrial dysfunction in human primary alveolar type II cells in emphysemaResearch in context - Beata Kosmider; Chih-Ru Lin; Loukmane Karim; Dhanendra Tomar; Liudmila Vlasenko; Nathaniel Marchetti; Sudhir Bolla; Muniswamy Madesh; Gerard J. Criner; Karim Bahmed (EBioMedicine, 2019)
Background: Cigarette smoke is the main risk factor of pulmonary emphysema development, which is characterized by alveolar wall destruction. Mitochondria are important for alveolar type II (ATII) cell metabolism due to ATP generation. Methods: We isolated ATII cells from control non-smoker and smoker organ donors, and after lung transplant of patients with emphysema to determine mitochondrial function, dynamics and mitochondrial (mt) DNA damage. Findings: We found high mitochondrial superoxide generation and mtDNA damage in ATII cells in emphysema. This correlated with decreased mtDNA amount. We also detected high TOP1-cc and low TDP1 levels in mitochondria in ATII cells in emphysema. This contributed to the decreased resolution of TOP1-cc leading to accumulation of mtDNA damage and mitochondrial dysfunction. Moreover, we used lung tissue obtained from areas with mild and severe emphysema from the same patients. We found a correlation between the impaired fusion and fission as indicated by low MFN1, OPA1, FIS1, and p-DRP1 levels and this disease severity. We detected lower TDP1 expression in severe compared to mild emphysema. Interpretation: We found high DNA damage and impairment of DNA damage repair in mitochondria in ATII cells isolated from emphysema patients, which contribute to abnormal mitochondrial dynamics. Our findings provide molecular mechanisms of mitochondrial dysfunction in this disease. Fund: This work was supported by National Institutes of Health (NIH) grant R01 HL118171 (B.K.) and the Catalyst Award from the American Lung Association (K.B.). Keywords: COPD, Emphysema, Lung, DNA damage, Alveolar type II cells, Mitochondria